The power of thanks : how social recognition empowers employees and creates a best place to work - Mosley, Eric; Irvine, Derek (McGraw-Hill Education, 2014)
This book reveals how leading companies like Intuit, JetBlue Airways, IHG, Symantec, ConAgra Foods, and The Hershey Company empower employees through social recognition, in which the practice of mutual appreciation and trust directs and rewards higher performance. The authors explain why social recognition is so powerful and how you can apply it in your company. Case by case, they show how a carefully planned and consistently executed Culture of Recognition business strategy inspires: greater employee engagement and loyalty; stronger, more unified teams and departments; a creative, innovative company culture; improved customer satisfaction; increased profitability and organizational health. Practical advice and proven examples for devising a powerful, growth-generating strategy that modernizes employee recognition for today's social, global, multi-generational and 24x7 wired workforce are provided. --